Cryptosporidium in goats from different farming systems in Terengganu - Hashim, Najat; Soffian, Sharmeen Nellisa; Hisamuddin, Nur Hazirah; Raja Abdul Rahman, Raja Nur Rahifah; Barudin, Mohd Aiman; Abdul Wahab, Ridhwan; Mohammad, Mardhiah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (2016)
This study was conducted to identify the presence of Cryptosporidium isolated from goats under different farming systems in Terengganu. A total of 200 fecal samples were randomly collected from goats in three farms (intensive, semi-intensive and extensive system). The samples were processed by using formol-ether concentration technique. Permanent stained slides were prepared using Modified Ziehl Neelsen stain. Out of 200 goats, 98 (49%) were found to be infected with Cryptosporidium. Goats reared under the extensive farm management system showed the highest prevalence of infection (56.7%), followed by the semi-intensive farm management system (51.4%) and the lowest prevalence was reported in the goats reared under the intensive farm management system (40%). The findings showed that goats reared under intensive system were less susceptible to cryptosporidiosis.